2021
DOI: 10.12998/wjcc.v9.i32.9762
|View full text |Cite
|
Sign up to set email alerts
|

Treatment effects and periodontal status of chronic periodontitis after routine Er:YAG laser-assisted therapy

Abstract: BACKGROUND Routine preclinical interventions for patients with chronic periodontitis such as supragingival cleaning and subgingival curettage, establishing a balanced occlusal relationship, and irrigation with 3% hydrogen peroxide can relieve the symptoms to some extent. However, there is room for improvement in the overall effect. For example, Er:YAG lasers can quickly increase the temperature of the irradiated tissue, effectively eliminate dental plaque and calculus, reduce periodontal pockets, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Recent epidemiological surveys show that more than half of adults worldwide suffer from gingivitis and periodontitis, with a trend toward younger adults [ 27 ]. Clinically, the main goal of periodontitis treatment is to inhibit plaque and eliminate inflammation to prevent deterioration and recurrence of the disease [ 28 ]. Given the potential for directed differentiation of MSCs, using gingiva MSCs was expected to be an effective solution for the radical treatment of periodontitis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent epidemiological surveys show that more than half of adults worldwide suffer from gingivitis and periodontitis, with a trend toward younger adults [ 27 ]. Clinically, the main goal of periodontitis treatment is to inhibit plaque and eliminate inflammation to prevent deterioration and recurrence of the disease [ 28 ]. Given the potential for directed differentiation of MSCs, using gingiva MSCs was expected to be an effective solution for the radical treatment of periodontitis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the laser main energy density is delivered laterally, keeping the deepest sulcus attachment moderately impacted by laser irradiation. It was also mentioned by Gao et al in 2021 that low energy levels delivered from the Er:YAG laser during root irradiation have no irreversible damage on periodontal tissues; on the contrary, it improves overall healing by reducing inflammatory factors and colony forming units [32]. Meanwhile, Yaneva et al in 2016 demonstrated the innocuity of pulp tissue to the energy level (100 mJ, 50 Hz, and 40 s irradiation time) higher than the ones used in our study [33].…”
Section: Discussionmentioning
confidence: 95%
“…For supragingival calculus, three treatment studies were included from a total of 197 articles. This includes one clinical practice guideline and two randomized controlled trials (RCTs) ( Supplementary Table S2 ) [ 12 , 13 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…AI produced similar treatment options, emphasizing the use of scalers to remove supragingival calculus [ 17 , 18 ]. Bard cited the EFP guidelines as the basis of their recommendations, denoting a commonality between the rapid review and AI [ 14 ]. However, variation existed in their recommendations for adjunctive treatment and risk factor management compared to the rapid review [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%